Diabetic macular edema treatment with subthreshold micropulse laser - five-year long monitoring - Martina Zavorkova; Jana Nekolova; Lidmila Prochazkova; Eva Cermakova; Nada Jiraskova (Biomedical Papers, 2023)
Aim. The objective of this study was to evaluate the efficacy of diabetic macular edema (DME) therapy using subthreshold micropulse laser (SMPL) with a wavelength of 577 nm during a long-term monitoring period of 5 years. Methods. The cohort included the total number of 52 eyes of 34 patients with DME. All underwent the standard laser treatment for the diabetic retinopathy outside the macula and DME treatment with SMPL. Subsequent check-ups were followed every 3 months in the first year of treatment, and every 4 to 6 months in the following years. The treatment was combined neither with focal macular laser nor with anti-VEGF therapy. Results. The mean central retinal thickness (CRT) was 345.9 µm SD 122.6 µm at the beginning of the monitoring. At the end of the follow-up period five years after treatment it was 256.4 µm SD 98.4 µm. The mean CRT decreased by 89.5 µm SD 153.6 µm during 5 years. At the beginning of the monitoring, before treatment with SMPL, the best corrected visual acuity (BCVA) was 70.0, SD 10.1 ETDRS letters. One year after therapy, BCVA was 72, SD 10.0 letters, two years later it was 71.4, SD 10.4 letters and decreased to 66.9, SD 12.1 letters after 5 years. The mean BCVA decreased by merely 3.1, SD 10.9 letters during 5 years. Conclusion. Based on our long-term observations, the DME treatment with SMPL appears to be an effective method for reducing DME and protecting BCVA against rapid worsening.